2013
DOI: 10.1016/j.euroecorev.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Taking the initiative. What characterizes leaders?

Abstract: Taking the initiative is a crucial element of leadership and an important asset for many jobs. We assess this element of leadership in a game in which it emerges spontaneously since people have a non-obvious possibility to take the initiative. We can show that leadership in this game correlates with real life activities associated with taking the initiative. Combining this game with other experimental games and with questionnaires, we investigate the personality characteristics that entail leadership. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
1
13
0
3
Order By: Relevance
“…Significance levels: + p < 0.10, * p < 0.05, * * p < 0.01, * * * p < 0.001. Sources: SOEP v30 1991-2013, UKHLS 2009, HILDA 2001. The bootstrapped (400 replications) δ R 2 values (computed as described in equation 10) for the combined importance of personality traits in the SOEP for all specifications estimated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significance levels: + p < 0.10, * p < 0.05, * * p < 0.01, * * * p < 0.001. Sources: SOEP v30 1991-2013, UKHLS 2009, HILDA 2001. The bootstrapped (400 replications) δ R 2 values (computed as described in equation 10) for the combined importance of personality traits in the SOEP for all specifications estimated.…”
Section: Resultsmentioning
confidence: 99%
“…Significance levels: + p < 0.10, * p < 0.05, * * p < 0.01, * * * p < 0.001. Sources: SOEP v30 1991-2013, UKHLS 2009, HILDA 2001. The effect of personality traits on wages with 90%-confidence intervals for the Australian sample with the EIV-correcion (corresponding to Table 13).…”
Section: B Explaining δ Rmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of Bruttel and Fischbacher (2013), persons as leaders are characterized by above-average cognitive skills and are predominantly male. They have strong preferences for efficiency, generosity, and against advantageous inequality, and do not primarily seek to maximize their personal monetary benefit or to obtain a positive public image.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, it can be shown that, the Pareto-dominant equilibrium outcome yields both Sel…sh and Other-Regarding players the same expected utility. 9 However, in the Nash stage-game equilibrium, Sel…sh players have a lower expected utility compared with Other-Regarding players, since the latter produce lower e¤orts, which increases the overall expected payo¤s. Hence, Sel…sh players have more to gain by coordinating on the Pareto-dominant equilibrium.…”
Section: Hypothesesmentioning
confidence: 99%